Internet and Social Media Use by Young People for Information about (Inter)National News and Politics in Russia and Kazakhstan - Sairambay, Yerkebulan (Studies of Transition States and Societies, 2022)
In this research note, I examine whether research conducted among young internet and social media users in Russia and Kazakhstan is representative of generalisable conclusions, particularly in relation to political participation studies. At present there is no reliable information on this topic in these societies. I commissioned four questions per country using omnibus surveys conducted in the 2020 autumn intake of the voting-age (18+) population using funding from the ‘Bolashaq’ programme. Based on the findings I procured through the omnibus surveys conducted by national public opinion poll companies (Levada Center and Central Asian Barometer) in Russia and Kazakhstan, my analysis shows that (1) more than 99% of all young people aged 18–29 use the internet and social media; and (2) nearly three out of four young people use social media for information about national and international news and politics. However, despite these high indicators, the frequency of the usage of social media for news and politics varies considerably in both countries. The paper with its up-to-date data as of 2021 fills a gap in Russian and Kazakhstani research, providing scholars with data to conduct further research about internet, social media, and politics among new media users. In addition, it provides a comparative analysis of the frequency of internet and social media use by young people for information about (inter)national news and politics in Russia and Kazakhstan.